Benz-amidinato calcium iodide catalyzed aldehyde and ketone hydroboration with unprecedented functional group tolerance - Yadav, S.; Pahar, S.; Sen, S. S. (Chemical Communications, 2017)
A benz-amidinato calcium compound, [PhC(NiPr)(2)Cal] (1), catalyzed hydroboration of a wide range of aldehydes and ketones using pinacolborane (HBpin) at room temperature is reported. The catalyst shows functional group tolerance even towards OH and NH groups. The strategy was further extended to imines.